The Ethics of Conflict Resolution in Dayak-Barai Customary Law in Pati Based on Habermas - Mathias Jebaru Adon; Yustina Ndung; Sonideritus Bandung; Fransiskus Gregorius Nyaming; Charles Virgenius Setiawan (Pancasila: Jurnal Keindonesiaan, 2026)
This study aims to analyse the Pati customary law of the Dayak-Barai tribe in West Kalimantan as a form of discourse ethics in the resolution of communal conflicts. Pati customary law prescribes sanctions against perpetrators who take another person’s life and serves as local wisdom to restore social harmony. This study employs a qualitative method through literature review and in-depth interviews with traditional leaders. The collected data is then analysed and interpreted using Habermas’s framework of discourse ethics. The results indicate that the Pati customary law incorporates deliberative practices reflecting communicative rationality, where conflicting parties are brought together in dialogue to reach a mutual understanding. The sanctions imposed are not merely punitive but restorative, aimed at preventing retaliation. This study also identified tensions between customary practices and the universal principles of discourse ethics, particularly regarding power imbalances, ritual elements, and the final authority of customary leaders. Nevertheless, Pati’s customary law continues to demonstrate a model of peaceful conflict resolution deeply rooted in local culture.